1975
DOI: 10.2135/cropsci1975.0011183x001500030015x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hydroxamic Acid Content in Maize and Resistance to Northern Corn Leaf Blight1

Abstract: A cyclic hydroxamate (2,4‐dihydroxy‐7‐methoxy‐l,4‐benzoxazin‐3‐one; DIMBOA) recently has been implicated in the resistance of maize (Zea mays L.) to fungi and insects. In our study, a set of 13 inbreds was used to determine the relationship of concentrations of DIMBOA and resistance to northern corn leaf blight (Helminthosporium turcicum Pass).DIMBOA concentration was estimated by the colorimettic procedure of Hamilton in plants 60 to 75 cm in height. Mean concentrations of DIMBOA ranged from 0.06 mg/g to 0.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…1) of DIMBOA. Our earlier work (20) has demonstrated that maize converts [2][3][4][5][6][7][8][9][10][11][12][13][14] Cindole into 14 C-DIMBOA, and that perdeuterated indole is converted by maize into DIMBOA that is deuterated both in the benzene ring and at the hemiacetal carbon of the heterocyclic ring. These results demonstrate that the DIMBOA biosynthetic pathway utilizes indole as a direct intermediate and raise the question of whether a specific indole synthase exists for this pathway or whether indole is diverted from the tryptophan biosynthetic pathway.…”
mentioning
confidence: 99%
“…1) of DIMBOA. Our earlier work (20) has demonstrated that maize converts [2][3][4][5][6][7][8][9][10][11][12][13][14] Cindole into 14 C-DIMBOA, and that perdeuterated indole is converted by maize into DIMBOA that is deuterated both in the benzene ring and at the hemiacetal carbon of the heterocyclic ring. These results demonstrate that the DIMBOA biosynthetic pathway utilizes indole as a direct intermediate and raise the question of whether a specific indole synthase exists for this pathway or whether indole is diverted from the tryptophan biosynthetic pathway.…”
mentioning
confidence: 99%
“…Although the physiological role of DIMBOA is unknown, various workers have postulated its involvement in: (a) detoxification of s-triazine herbicides (21,26); (b) iron transport (25); (c) resistance to fungal infection in corn and wheat (2,7,8,20); and (d) as a factor in insect resistance (17,19). Because of the instability of DIMBOA, Whitney and Mortimore (30) have postulated that its degradation product, MBOA, may be involved in the resistance of corn to bacteria.…”
mentioning
confidence: 99%
“…Physical injury by a biting, chewing, or sucking insect or cell lysis after fungal and bacterial infections disrupts the compartmentalization and brings the enzyme and substrate in contact, releasing the toxic aglycone DIMBOA. Numerous studies show a high correlation between DIMBOA content of maize genotypes and the level of resistance to or inhibitory effect on insects and pathogens (Klun et al, 1967;Long et al, 1975;Argandona et al, 1983;Niemeyer, 1991).…”
mentioning
confidence: 99%